Liedtexte in der Übersetzung am Beispiel des Liedes „Ein bisschen Frieden“ und dessen Covers „Troszeczkę ziemi, troszeczkę słońca“ - Rafał Adamski (Linguistische Treffen in Wrocław, 2025)
The aim of this article is to analyze the phenomenon of cover songs as translations of song lyrics. Using the cover version “Troszeczkę ziemi, troszeczkę słońca” by Eleni and the original “Ein bisschen Frieden” by Nicole, the linguistic and cultural adaptation of lyrics in cover versions is examined. The article highlights that cover songs are not only musical reinterpretations but also translations that consider the cultural and linguistic context of the target culture. The methodology includes a comparative analysis of the Polish cover and the German original based on five specific criteria that address linguistic and translational aspects. The results show that cover songs can be regarded as translations, as they transfer both the meaning and the emotional impact of the original into another language. This article provides a valuable contribution to existing research by bringing the often-overlooked phenomenon of cover versions as translations to the forefront. While translation studies have predominantly focused on literary translations, it is demonstrated here that cover songs represent an equally significant form of linguistic and cultural translation. This perspective expands the understanding of translation processes and opens up a new area for future research. The paper emphasizes the need to analyze more songs in a similar way and to focus more on intercultural exchange through music within the field of translation studies.